Tomoelastography for the Evaluation of Pediatric Nonalcoholic Fatty Liver Disease. Issue 4 (April 2019) - Hudert, Christian A.; Tzschätzsch, Heiko; Rudolph, Birgit; Bläker, Hendrik; Loddenkemper, Christoph; Müller, Hans-Peter; Henning, Stephan; Bufler, Philip; Hamm, Bernd; Braun, Jürgen; Holzhütter, Hermann-Georg; Wiegand, Susanna; et al.
Abstract : Objectives: Today, nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in children and adults alike. Yet, the noninvasive evaluation of disease severity remains a diagnostic challenge. In this study, we apply multifrequency magnetic resonance elastography (mMRE) for the quantification of liver steatosis and fibrosis in adolescents with NAFLD. Methods: Fifty adolescents (age range, 10–17 years; mean BMI, 33.9 kg/m 2 ; range, 21.4–42.1 kg/m 2 ) with biopsy-proven NAFLD were included in this prospective study. Multifrequency magnetic resonance elastography was performed using external multifrequency vibrations of 30 to 60 Hz and tomoelastography postprocessing, resulting in penetration rate ( a ) and shear wave speed ( c ). Hepatic fat fraction was determined using Dixon method. The diagnostic accuracy of mMRE in grading liver steatosis and staging liver fibrosis was assessed by receiver operating characteristic curve analysis. Results: Multifrequency magnetic resonance elastography parameters c and a were independently sensitive to fibrosis and steatosis, respectively, providing area under the receiver operating characteristic values of 0.79 (95% confidence interval [CI], 0.66–0.92), 0.91 (95% CI, 0.83–0.99), and 0.90 (95% CI, 0.80–0.99) for the detection of any (≥F1), moderate (≥F2), and advanced (≥F3) fibrosis, and 0.87 (95% CI, 0.76–0.97) and 0.87 (95% CI, 0.77–0.96) for the detection of moderate (≥S2) and severe (S3) steatosis. Conclusions: One mMRE measurement provides 2 independent parameters with very good diagnostic accuracy in detecting moderate and advanced fibrosis as well as moderate and severe steatosis in pediatric NAFLD. Abstract : Supplemental digital content is available in the text.